Penerapan Prinsip Proporsionalitas Hukum Humaniter Internasional dalam Perang Rusia - Ukraina - Nurhayati, Ema (PMIH Untag Semarang, 2024)
The principle of proportionality is one of the fundamental pillars in international humanitarian law that aims to minimize unnecessary suffering and damage in armed conflict situations. The principle of proportionality, which requires a balance between military advantage and civilian harm, has become a primary focus in the war between Russia and Ukraine, given widespread reports of attacks on civilian infrastructure. The research objective is to analyze the application of the principle of proportionality in the Russia-Ukraine war and identify challenges in its implementation. This research methodology is normative method, analyzing international legal documents, human rights organization reports, and specific case studies from the conflict. The main findings indicate violations of the principle of proportionality by both sides, especially in attacks on densely populated areas and critical infrastructure. However, the research also reveals difficulties in objectively assessing proportionality due to the complexity of modern conflicts and limited access to information. In conclusion, although the principle of proportionality remains a key standard in international humanitarian law, its application in the Russia-Ukraine war demonstrates the need for more effective assessment and enforcement mechanisms. This research highlights the importance of updating the legal framework to address the challenges of contemporary conflicts.